Rectangular sources and systems of sound sources with large directionality - Andrzej PUCH (Archives of Acoustics)
This paper presents a method for constructing plane, rectangular sound sources with large directionality of vibration energy radiation into the far field. The directional properties of sound sources of this type were analysed for uniform, Hanning and Blackmann distributions of the vibration velocity amplitude on their surface. It was found that a rectangular sound source with large directionality of vibration energy radiation into the far field can be realised in practice in the form of a plane, rectangular mosaic system of sound sources with a discrete Hanning distribution of their relative bulk efficiencies.